Electronic fibers and textiles: Recent progress and perspective - Zhang, Yong; Wang, Huimin; Lu, Haojie; Li, Shuo; Zhang, Yingying (iScience, 2021)
Wearable electronics are receiving increasing attention with the advances of human society and technologies. Among various types of wearable electronics, electronic fibers/textiles, which integrate the comfort and appearance of conventional fibers/textiles with the functions of electronic devices, are expected to play important roles in remote health monitoring, disease diagnosis/treatment, and human-machine interface. This article aims to review the recent advances in electronic fibers/textiles, thus providing a comprehensive guiding reference for future work. First, we review the selection of functional materials and fabrication strategies of fiber-shaped electronic devices with emphasis on the newly developed functional materials and technologies. Their applications in sensing, light emitting, energy harvest, and energy storage are discussed. Then, the fabrication strategies and applications of electronic textiles are summarized. Furthermore, the integration of multifunctional electronic textiles and their applications are summarized. Finally, we discuss the existing challenges and propose the future development of electronic fibers/textiles. [Display omitted] Materials property; Electronic materials; Fibrous material